Farming Systems Research into the 21st Century: The New Dynamic - Darnhofer, Ika; Gibbon, David; Dedieu, Benoît (Springer Netherlands : Imprint: Springer, 2012)
Farming Systems Research has three core characteristics: it builds on systems thinking, it depends on the close collaboration between social and biophysical sciences, and it relies on participation to build co-learning processes. Farming Systems Research posits that to contribute towards sustainable rural development, both interdisciplinary collaborations and local actor engagement are needed. Together, they allow for changes in understanding and changes in practices. This book gives an overview of the insights generated in 20 years of Farming Systems Research. It retraces the emergence and development of Farming Systems Research in Europe, summarises the state-of-the-art for key areas, and provides an outlook on new explorations, especially those tackling the dynamic nature of farming systems and their interaction with the natural environment and the context of action. We hope this book will serve as an inspiration for all those who seek an alternative approach to research in farming and rural development. One that builds on the reflexivity of researchers, one that takes the role of human subjectivities and perceptions seriously, one that gives voice to farmers, one that emphasises participation and co-learning processes, one that focuses on interactions between the elements, one that allows to capture interdependencies and their dynamics. There is no doubt that Farming Systems Research has much to offer to answer the challenges faced by rural areas in the current turbulent and uncertain times. The book is thus aimed at practitioners, at graduate students and at researchers who seek new inspiration outside the mainstream, who take into account the ethical dimension of their work, and who seek encouragement to deepen their reflexivity about the meaning of professional practice and about their approach to research.